Mitochondrial F-type ATP synthase: multiple enzyme functions revealed by the membrane-embedded FO structure. (3rd July 2020) - Nesci, Salvatore; Pagliarani, Alessandra; Algieri, Cristina; Trombetti, Fabiana
Abstract: Of the two main sectors of the F-type ATP synthase, the membrane-intrinsic FO domain is the one which, during evolution, has undergone the highest structural variations and changes in subunit composition. The FO complexity in mitochondria is apparently related to additional enzyme functions that lack in bacterial and thylakoid complexes. Indeed, the F-type ATP synthase has the main bioenergetic role to synthesize ATP by exploiting the electrochemical gradient built by respiratory complexes. The FO membrane domain, essential in the enzyme machinery, also participates in the bioenergetic cost of synthesizing ATP and in the formation of the cristae, thus contributing to mitochondrial morphology. The recent enzyme involvement in a high-conductance channel, which forms in the inner mitochondrial membrane and promotes the mitochondrial permeability transition, highlights a new F-type ATP synthase role. Point mutations which cause amino acid substitutions in FO subunits produce mitochondrial dysfunctions and lead to severe pathologies. The FO variability in different species, pointed out by cryo-EM analysis, mirrors the multiple enzyme functions and opens a new scenario in mitochondrial biology.